Impact of the lung oncology multidisciplinary team meetings on the management of patients with cancer. Issue 2 (27th March 2014) - Ung, Kim Ann; Campbell, Belinda A; Duplan, Danny; Ball, David; David, Steven
Abstract: Aims: Multidisciplinary team (MDT) meetings are increasingly regarded as a component of multidisciplinary cancer care. We aimed to prospectively measure the impact of MDT meetings on clinicians' management plans for lung oncology patients, and the implementation rate of the meeting recommendations. Methods: Consecutive patient cases presented at the weekly lung oncology MDT meetings were prospectively enrolled. Investigators compared the clinicians' management plans pre‐meeting with the consensus plans post‐meeting. The meeting was considered to have an impact on management plans if ≥1 of the following changes were detected: tumor stage, histology, treatment intent or treatment modality, or if additional investigations were recommended. Investigators reviewed hospital patient records at 4 months to determine if the meeting recommendations were implemented. Reasons for non‐implementation were also recorded. Results: Of the 55 eligible cases, the MDT meeting changed management plans in 58% (CI 45–71%; P  < 0.005). These changes included: additional investigations (59%), or changes in treatment modality (19%), treatment intent (9%), histology (6%) or tumor stage (6%). The meeting recommendations were implemented in 72% of cases. Reasons for non‐implementation included deteriorating patient performance status, clinician's preference, the influence of new clinical information obtained after the meeting or patient decision. Conclusion: MDT meetings significantly impact on the management plans for lung oncology patients. The majority of MDT recommendations (72%) were implemented into patient care. These findings provide further evidence to support the role of MDT meetings as an essential part of the decision‐making process for the optimal multidisciplinary management of patients with cancer.